2020
DOI: 10.1136/jitc-2019-000348
|View full text |Cite
|
Sign up to set email alerts
|

Biomarkers for immunotherapy for treatment of glioblastoma

Abstract: Immunotherapy is a promising new therapeutic field that has demonstrated significant benefits in many solid-tumor malignancies, such as metastatic melanoma and non-small cell lung cancer. However, only a subset of these patients responds to treatment. Glioblastoma (GBM) is the most common malignant primary brain tumor with a poor prognosis of 14.6 months and few treatment advancements over the last 10 years. There are many clinical trials testing immune therapies in GBM, but patient responses in these studies … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
41
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(45 citation statements)
references
References 149 publications
0
41
0
Order By: Relevance
“…In recent decades, despite continuous improvements in neurosurgery techniques and innovations in new treatment methods, such as immunotherapy and molecular-targeted therapy, the survival time of patients with GBM is still not optimistic. 2,29,30 It is noteworthy that a certain number of GBM patients with good preoperative and postoperative Abbreviations: NLR, the neutrophil-to-lymphocyte ratio; PLR, the platelet-tolymphocyte ratio; LMR, the lymphocyte -to-monocyte ratio; PNI, the prognostic nutrition index; AGR, albumin-to-globulin ratio; RDW, red blood cell distribution width; GLC, glucose; LDH, lactate dehydrogenase; FIB, fibrinogen; DD, D-dimer. health status, who received standard treatment protocols, should have better clinical outcomes, but instead had an endpoint event ie, death within 1 year.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In recent decades, despite continuous improvements in neurosurgery techniques and innovations in new treatment methods, such as immunotherapy and molecular-targeted therapy, the survival time of patients with GBM is still not optimistic. 2,29,30 It is noteworthy that a certain number of GBM patients with good preoperative and postoperative Abbreviations: NLR, the neutrophil-to-lymphocyte ratio; PLR, the platelet-tolymphocyte ratio; LMR, the lymphocyte -to-monocyte ratio; PNI, the prognostic nutrition index; AGR, albumin-to-globulin ratio; RDW, red blood cell distribution width; GLC, glucose; LDH, lactate dehydrogenase; FIB, fibrinogen; DD, D-dimer. health status, who received standard treatment protocols, should have better clinical outcomes, but instead had an endpoint event ie, death within 1 year.…”
Section: Discussionmentioning
confidence: 99%
“…In recent decades, despite continuous improvements in neurosurgery techniques and innovations in new treatment methods, such as immunotherapy and molecular-targeted therapy, the survival time of patients with GBM is still not optimistic. 2 , 29 , 30 It is noteworthy that a certain number of GBM patients with good preoperative and postoperative health status, who received standard treatment protocols, should have better clinical outcomes, but instead had an endpoint event ie, death within 1 year. Thus, we focused on IDH-wt GBM patients with preoperative and postoperative KPS scores ≥70 (ECOG PS scores ≥ 1) and receiving standard treatment including GTR, followed by concurrent chemoradiotherapy and adjuvant temozolomide.…”
Section: Discussionmentioning
confidence: 99%
“…In recent decades, despite continuous improvements in neurosurgery techniques and innovations in new treatment methods, such as immunotherapy and molecular-targeted therapy, the survival time of patients with GBM is still not optimistic (4,29,30). Accumulating studies have demonstrated that peripheral blood test parameters play a remarkable role in the prognosis of various malignant tumors, such as lung cancer, gastric cancer, colorectal cancer, and hepatocellular carcinoma, as well as GBM (12)(13)(14)(15)(31)(32)(33).…”
Section: Discussionmentioning
confidence: 99%
“…Vaccination of glioblastoma patients with a peptide mimicking the EGFR variant III (EGFRvIII) in glioblastoma cells, together with standard temozolomide chemotherapy or the anti-angiogenic agent bevacizumab, showed promising anti-glioblastoma effects in clinical trials. As only 25–30% of patients express EGFRvIII, and its expression is heterogeneous in tumors and unstable through the course of the disease, the efficiency of these vaccines is limited [ 72 , 73 ]. Moreover, a randomized, double-blind, and international phase 3 trial, which assessed the efficacy of the vaccine, based on EGFRvIII-specific peptide (CDX-110), with temozolomide did not show a survival benefit for newly diagnosed glioblastoma patients with EGFRvIII mutation [ 74 ].…”
Section: Immunotherapeutic Strategies For Glioblastomamentioning
confidence: 99%